Read, reason, write - Seyler, Dorothy U (McGraw-Hill Higher Education, 2010)
Includes bibliographical references and index; Read, Reason, Write unites instruction in critical reading and analysis, argument, and research strategies with a rich collection of readings that provide both practice for these skills and new ideas and insights for readers